Do People High in Dark Traits Have a Better Life? The Role of Dark Personality Traits on Objective and Subjective Career Success in an Indonesian Collective Society - Siti Nuzulia; Rahmawati Prihastuty; Aji Sofanudin; Thoriq Ibrahim Farras (Universitas Ahmad Dahlan, 2024)
Maintaining harmony in social relations, a fundamental value of a collective society, is completely opposed to the dark personality traits that are egocentric and antisocial. This fact has an impact on criticism and increased social pressure for individuals with dark personalities in a collective society, as well as on objective and subjective success. This cross-sectional study was conducted to elucidate the impact of dark personalities on success in a collective society. The results (N = 522) revealed that dark personality traits, particularly narcissism, were the most consistent traits in predicting subjective career success in participants with (n = 273) or without managerial positions (n = 249). Furthermore, participants with and without managerial positions showed no difference in subjective career success. The findings are expected to provide reliable information on the influence of dark personalities on success in a collective society. Keywords: dark personality, narcissism, Machiavellianism, psychopathy, career success